Young children's self‐benefiting lies and their relation to executive functioning and theory of mind. Issue 1 (1st August 2017) - Fu, Genyue; Sai, Liyang; Yuan, Fang; Lee, Kang
Abstract: It is well established that children lie in different social contexts for various purposes from the age of 2 years. Surprisingly, little is known about whether very young children will spontaneously lie for personal gain, how self‐benefiting lies emerge, and what cognitive factors affect the emergence of self‐benefiting lies. To bridge this gap in the literature, we situated children between 2 and 4 years of age in a zero‐sum game where children must lie to their opponent if they wanted to win a desirable reward. We found that the majority of young children did not lie even when they experienced personal losses repeatedly. However, some children spontaneously lied during the game; as the game progressed, more children lied. Further, we found that children's theory of mind understanding and executive functioning in terms of a combination of inhibitory control and cognitive flexibility had significant positive and unique correlations with how frequently children lied for personal gain. The present results taken together with the existing findings regarding children's lies for self‐protection and politeness purposes suggest that the act of lying begins early in life. Further, its emergence and development are influenced by children's specific cognitive abilities in the domains of theory of mind understanding and executive functioning. Highlights: The study investigated whether very young children will spontaneously lie for personal gain. This study used a zero‐sum game to elicit children's self‐benefiting lies. Results showed the majority of young children did not lie, and it is related to children's theory of mind understanding and executive functioning. The act of lying begins early in life, and its emergence and development are influenced by children's specific cognitive abilities in the domains of theory of mind understanding and executive functioning.